A modal-based Partition of Unity Finite Element Method for elastic wave propagation problems in layered media. (June 2022) - Destuynder, P.; Hervella-Nieto, L.; López-Pérez, P.M.; Orellana, J.; Prieto, A.
Highlights: A modal basis and a Partition of Unity Finite Element Method are combined. The tensorial form of Love and internal eigenmodes of a bilayered material are used. Condition number for the stiffness matrix is estimated a priori. Some regularization techniques are analyzed in different discrete scenarios. The modal basis can be selected in terms of the interface crack observability. Abstract: The time-harmonic propagation of elastic waves in layered media is simulated numerically by means of a modal-based Partition of Unity Finite Element Method (PUFEM). Instead of using the standard plane waves or the Bessel solutions of the Helmholtz equation to design the discretization basis, the proposed modal-based PUFEM explicitly uses the tensor-product expressions of the eigenmodes (the so-called Love and interior modes) of a spectral elastic transverse problem, which fulfil the coupling conditions among layers. This modal-based PUFEM approach does not introduce quadrature errors since the coefficients of the discrete matrices are computed in closed-form. A preliminary analysis of the high condition number suffered by the proposed method is also analyzed in terms of the mesh size and the number of eigenmodes involved in the discretization. The numerical methodology is validated through a number of test scenarios, where the reliability of the proposed PUFEM method is discussed by considering different modal basis and source terms. Finally, some indicators are introduced to select a convenient discrete PUFEM basis taking into account the observability of cracks located on a coupling boundary between two adjacent layers.